2011
DOI: 10.2319/120610-703.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mandibular incisor intrusion obtained using a conventional utility arch vs bone anchorage

Abstract: To compare the dentofacial effects of mandibular incisor intrusion using mini-implants with those of a conventional incisor intrusion mechanic, the utility arch. Materials and Methods: Twenty-six deep-bite patients were enrolled to one of the two groups. In group 1 the mandibular incisors were intruded using a 0.16 3 0.22-inch stainless-steel segmental wire connected to two mini-implants. In group 2 the mandibular incisor intrusion was performed using a conventional utility arch. Conventional lateral cephalome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 16 publications
0
20
2
1
Order By: Relevance
“…According to quantitative synthesis, miniscrews had a greater overall effect on reducing overbites than did the intrusion arches. Similarly, Aydogdu andÖzsoy 24 found that miniscrews resulted in a similar amount of deep-bite correction compared with conventional utility arches during intrusion of mandibular incisors. Howev- er, they had to place their miniscrews in a strictly narrower interradicular space between the mandibular incisors; thus, some difficulties might have been expressed in sustaining the miniscrews.…”
Section: Discussionmentioning
confidence: 85%
“…According to quantitative synthesis, miniscrews had a greater overall effect on reducing overbites than did the intrusion arches. Similarly, Aydogdu andÖzsoy 24 found that miniscrews resulted in a similar amount of deep-bite correction compared with conventional utility arches during intrusion of mandibular incisors. Howev- er, they had to place their miniscrews in a strictly narrower interradicular space between the mandibular incisors; thus, some difficulties might have been expressed in sustaining the miniscrews.…”
Section: Discussionmentioning
confidence: 85%
“…Tip-back bends and base arches are some of the mechanics that have been suggested for the extrusion of posterior teeth [10][11][12][13] . In order to intrude the incisors, J-hook headgears, functional appliances, anterior bite-planes, segmented arch technique, Begg mechanics, edgewise mechanics, three piece base arch, utility intrusion arch, connecticut intrusion arch, and temporary anchorage device can be used [14][15][16][17][18][19][20][21][22] . The specific treatment objectives need to be determined before the mechanotherapy is initiated.…”
Section: Introductionmentioning
confidence: 99%
“…Los brackets de autoligado activo, donde la plancha de cierre ejerce una presión sobre el arco que le obliga a tomar contacto con la base del slot, generan mayor fricción que con las que no aplican tal fuerza (1,22). Dicho de otra manera, a mayor asentamiento del arco en el surco, mayor fricción se genera por el contacto de la superficie plana del arco con la superficie plana de la base del slot (2).…”
Section: Cubierta De Polímerounclassified